GAMBARAN PEMBERIAN PRELAKTEAL PADA NEONATUS DI WILAYAH KERJA PUSKESMAS REJOSARI PEKANBARU - Wisda Elviani; Yesi Hasneli; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Neonates are newborns aged up to 28 days (4 weeks). At this time, neonates need to be given breast milk which has high amount of colostrum that contains antibodies, anti-infectives and immunoglobulins to maintain their health. However, the case of breastfeeding the infants is still very low, this is partly due to prelacteal distribution. Prelacteal is food or drink other than breast milk that is given to infants 1-3 days after birth. This study aimed to determine the description of prelacteal delivery to neonates in the working area of Rejosari Health Center, Pekanbaru. This study used a quantitative research design with descriptive method, and with a retrospective approach. The number of samples was 48 mothers who had prelacteal given to their neonates. The measuring instrument was questionnaire. The results of this study found that 36 people (75.0%) gave prelacteal on the first day; with a duration of 1-2 days, given by 25 people (52.1%) and the type of prelacteal given in the form of infant formula (milk) were given by 37 people (77.1%), and due to the unavailability of the breast milk and was recommended by health workers were 24 people (50.0%). The results of this study recommended mothers who have neonates to give exclusive breastfeeding instead of prelacteal, and to health workers, especially nurses in health centers to make more efforts promoting exclusive breastfeeding for neonates and give more health educations about prevention of giving prelacteal to neonates. Keywords: neonates, prelacteal